RFID reader architectures and applications - Reaz, Mamun Bin Ibne; Uddin, Md. Jasim; Hussain Shah, Qasim; Nordin, Anis Nurashikin; Ibrahimy, Muhammad Ibn; Mohd-Yasin, Faisal (Horizon House Publications, 2009)
In order to use radio frequency identification (RFID) for wireless communication and real world applications such as supply chain management, asset tracking systems, security and privacy systems, healthcare and commercial pplications, library management systems, geographic surface location identification and industrial tracking systems, the study of the nature and characteristics of the reader is an important factor. The purpose of this article is to review and discuss various methodologies aimed at developing the reader’s components and remove its interference. It further focuses on the review of future implementation methodologies and performance comparison along with their applications. Some of the applications are illustrated at the end of the article and recommendations for further study are also outlined. It will serve as a comparative study and reference for future implementation of the technology, beneficial to RFID reader researchers. It opens a corridor for researchers to perform future comparative studies between different architectures and models as a reference point for developing more powerful, flexible and efficient applications.